2022
DOI: 10.58220/jba.v15i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Translation Procedures of Economic Article from English into Indonesian

Abstract: This research aims to analyze the translation procedures of economic articles from English into Indonesian by the fourth semester students 2020/2021 in STBA JIA. The data will be analyzed by the theory of Vinay and Darbelnet about translation procedures. This research is qualitative research with descriptive analysis, which gives more attention on how deep the translation’s knowledge towards the concept which was being learned and how the theory is used to translate the article. The data of the research is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…have been the topic of many pieces of national and international studies over the past decade, indicating the topic's importance in the study of translation, particularly audiovisual translation. It was included the in research conducted by Ávila-Cabrera (2015); Timur (2016); Rachmawaty (2018); Robingah (2019); Slamia (2020); Alsharhan (2020); and Tigana andWahyuningsih (2022). First, Ávila-Cabrera (2015), in his research entitled Subtitling Tarantino's Offensive and Taboo Dialogue Exchanges into European Spanish: The Case Mantika, A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been the topic of many pieces of national and international studies over the past decade, indicating the topic's importance in the study of translation, particularly audiovisual translation. It was included the in research conducted by Ávila-Cabrera (2015); Timur (2016); Rachmawaty (2018); Robingah (2019); Slamia (2020); Alsharhan (2020); and Tigana andWahyuningsih (2022). First, Ávila-Cabrera (2015), in his research entitled Subtitling Tarantino's Offensive and Taboo Dialogue Exchanges into European Spanish: The Case Mantika, A.…”
Section: Introductionmentioning
confidence: 99%
“…In the results, he found that there were 868 data of taboo languages with retention strategy (2.65% data), direct translation strategy (21.89%), substitution strategy (22%), paraphrase strategy (13.02%), standardization strategy (4.61%), generalization strategy (11.87%), specification strategy (14.4%), and omission strategy (9.56%). The seventh study is done by Tigana and Wahyuningsih (2022), entitled A Translation Analysis of the Slang Words in the Master of None: Season 1 TV Series Subtitles From English To Indonesian. They focused on analyzing slang words in the TV series called Master of None.…”
Section: Introductionmentioning
confidence: 99%
“…(2023). Annotated Translation from Indonesia into English: The Tourism and Culture Office's Website of Bekasi.YeniNoryatin, Inta Masni Sinaga, Ceicilia Putri Cahyani. (2023).…”
mentioning
confidence: 99%